Risk Factors for Substance Abuse Among Youth: A Social Work Approach (ISJN Journal, 2022)
Social Work is a profession that aims to helping people to help themselves. Social work education has its own values and principles. Professional Social Workers have rendered their professional service in almost all areas. Presently, the youth of the nation are encountering many problems, such as violence, ignorance, HIV/AIDS, and drug abuse. The Drug abuse is not compressed to any one nation. All developed, developing, and even underdeveloped countries are encountering the problem. Abuse is a problem where we need to put our eyes on prevention. The present study aims to find the risk factors for substance use among youths in Tumkuru City, Karnataka. To fulfill the objective of the study, the researcher has conducted 2 focused group discussions (FGD). Each group consist of16 members. The age range of the participants is 18 to 40 years. Only male participants were involved in FGD. A study has found that many risk factors for substance use exist among youths. Such as peer groups influence, environment of community and the media has a significant influence on youths for substance use. Therefore, the social work profession has a vast scope to tackle this problem through Social Work approaches at the micro, mezzo, and macro level of intervention.